Dedifferentiated liposarcoma in the extremity and trunk wall: A multi-institutional study of 132 cases by the Japanese Musculoskeletal Oncology Group (JMOG). Issue 2 (February 2023) - Morii, Takeshi; Anazawa, Ukei; Sato, Chiaki; Iwata, Shintaro; Nakagawa, Makoto; Endo, Makoto; Nakamura, Tomoki; Ikuta, Kunihiro; Nishida, Yoshihiro; Nakayama, Robert; Udaka, Toru; Kawamoto, Teruya; et al.
Abstract: Background: Dedifferentiated liposarcoma occurs predominantly in the retroperitoneum. Given the paucity of cases, information on the clinical characteristics of this entity in the extremities and trunk wall is quite limited. In particular, the significance of preoperative evaluation and principles of intraoperative management of the different components, i.e., well-differentiated and dedifferentiated areas, are still to be defined. Methods: Clinical characteristics, treatment outcomes, and risk factors for poor oncological outcomes in cases of dedifferentiated liposarcoma in the extremity or trunk wall were analyzed by a retrospective, multicentric study. Results: A total of 132 patients were included. The mean duration from the initial presentation to dedifferentiation was 101 months in dedifferentiation-type cases. The 5-year local recurrence-free survival, metastasis-free survival, and disease-specific survival rates were 71.6%, 75.7%, and 84.7%, respectively. Among 32 patients with metastasis, 15 presented with extrapulmonary metastasis. A percentage of dedifferentiated area over 87.5%, marginal/intralesional margin, and R1/2 resection in the dedifferentiated area were independent risk factors for local recurrence. Dedifferentiated areas over 36 cm 2, French Federation of Cancer Centers Sarcoma Group grade III, and intralesional or marginal resection were independent risk factors for metastasis. A dedifferentiated area over 77 cm 2 and lung metastasis were independent risk factors for disease-specific mortality. Conclusions: The typical clinical characteristics of dedifferentiated liposarcoma in the extremity and trunk wall were reconfirmed in the largest cohort ever. The evaluation of the dedifferentiated area in terms of grade, extension, and pathological margin, together with securing adequate surgical margins, was critical in the management of this entity. Highlights: ● The mean time to dedifferentiation was 101 months in dedifferentiation type. ● The 5-year local recurrence and metastasis-free survival were 71.6% and 75.7%. ● The 5-year disease-specific survival rate was 84.7%. ● Among 32 patients with metastasis, 15 presented with extrapulmonary metastasis. ● Grade, extension, and margin in the dedifferentiated area are critical to outcomes.